mTORC1 Enhances Early Phase Ribosome Processivity - An, Erin; Friend, Kyle (Frontiers in Molecular Biosciences, 2020)
During translation elongation, the ribosome serially adds amino acids to a growing polypeptide over many rounds of catalysis. The ribosome remains bound to mRNAs over these multiple catalytic cycles, requiring high processivity. Despite its importance to translation, relatively little is known about how mRNA sequences or signaling pathways might enhance or reduce ribosome processivity. Here, we describe a metric for ribosome processivity, the ribosome processivity index (RPI), which is readily calculated from ribosomal profiling data. We show that ribosome processivity is not strongly influenced by open-reading frame (ORF) length or codon optimality. However, we do observe that ribosome processivity exists in two phases and that the early phase of ribosome processivity is enhanced by mTORC1, a key translational regulator. By showing that ribosome processivity is regulated, our findings suggest an additional layer of control that the cell can exert to govern gene expression.